Survey on common causative agents of dermatophytosis in El-Beida Libya - Bubaker, Khawila S. O. (Al-Mukhtar Journal of Sciences, 2019)
The aim of this study was to isolate and identify dermatomycosis causing dermatophysis in EL- Beida, Libya. In this study 253 cases of skin infection were collected from the dermatology unit at EL- Thoura hospital in EL- Beida, Libya. These cases clinically diagnosed as superficial mycosis ,130 ( 51.4%) were isolated from males and 123 ( 48.6% ) were females. These cases were classified into 5 groups according to age (1-10, 11-20, 21-31, 31-40 and above 40 year). Our results showed that young ages were more liable to infection than adult. The cases involved in this investigation represented different occupations. The highest incidence was recorded between school children 40.3 %, followed by workers, farmers and others 29.2%, house wives 17.8% while it was 12.6% among children less than 5 years. Concerning the clinical and mycological finding, it was noticed that 74 (63.8%) cases gave positive culture while the remaining cases were negative. Scalp infection was the most common clinical finding, in this study Tinea capitis was the most frequent 42.8% cases, Microsporum canis and Trich ophyton violaceum were the most common fungi isolated. Tinea corporis and Tinea cruris were diagnosed clinically in 68 (26.8%) cases, 24.4% were from Tinea corporis while the fungus isolated were Microsporum canis 41% , Epidermophyton floccosum 14% and Tinea cruris with incidence of 0.8% in which Trichophyton tonsurans was the only fungus isolated . Onychomycosis and Tinea pedis were seen in 3.4% and the most important isolated agents were Epidermophyton floccosum 50%, followed by Microsporum canis and Trichophyton rubrum 25% for each. This study demonstrates that the prevalence of dermatophytoses in EL- Beida cit, was high (47%), and was more common in males than females. The present study has also indicated that tinea capitis was the dominant (43%).